Optimal välfärd och hälsa för kalvar - Fredriksson, Martin (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
In order to optimize calf welfare and health it is important to know the behavior of cattle in free ranging conditions. When the cow is about to give birth to a calf she will leave the heard about 12 hours before. It is then rather obvious that isolating the cow about calving time in a single pen is imitating the cows' natural behavior. To save space and minimize building cost it's common that the farmers build calving pens for four of five cows especially at larger farms. In the calving pen, it is important to use lots of straw to avoid injuries on the cow and her calf. Covered walls will also minimize wind borne disease in the pen. The new born calf needs colostrum of adequate quality within six hours after birth. It's also important that the colostrum comes from the first milking since this milk has a higher concentration of immunoglobulin. Colostrum fed by hand is the only way to secure a proper immunization the calf. It is also very important to let the calf have access to water. A calf that has the opportunity to drink water early on learns to eat hay and concentrate which is favorable for the development of rumination. There are several ways to keep housed calves. The most common way has been a single pen where the calf is fed from a bucket. The calf health is very good in this system but lots of work with feeding and cleaning is needed and calf welfare is compromised as it has no social contact with other calves and very little space to perform play behavior. An automated calf feeder and the keeping of calves in groups is very effective way of breeding calves as it saves work and the calf has contact with other calves. However, there is a risk that health can deteriorate. To maintain good health, the group should not be too large and the difference in the age between the calves should not bee too large. By keeping calves in pairs, health is at low risk and still the calf can perform social and play behavior. To overcome health problems in a herd, calves can be kept in hutches outdoors. But, this system needs a lot of work. Another way is to use a suckler cow nursing several calves. Here, the calf health is very good and the calf will also be able to perform natural behavior. Calves also have large growth rates in this system. Generally, diarrhea and pneumonia are the most common health problem for calves. Proper immunization of the calf from good quality colostrum will prevent and reduce the number of calves becoming ill. Calf welfare includes the promotion of health and behaviour but other factors has to be taken into account as working time and performance but there are no direct contradictions.